The Connection Between Jordan Derivations and Nilpotent Derivations on 2-Torsion-Free Semiprime Rings - Rahmah Mutiara Ayu Ningtiyas; Fitriani Fitriani; Ahmad Faisol (Jambura Journal of Mathematics, 2025)
Let R be a ring. A derivation on a ring is an additive map that satisfies the Leibniz rule d(ab) = d(a)b + ad(b), for every a, b ∈ R. A derivation d on a ring R is called a nilpotent derivation if there exists a natural number n such that dⁿ(R) = 0. This research studies nilpotent Jordan derivations on 2-torsion-free semiprime rings. Motivated by the results of Brešar, Chung, and Luh on Jordan derivations and nilpotent derivations, the study aims to analyze their nilpotency patterns and the behavior of inner derivations generated by nilpotent elements. Using a deductive literature-study approach through mathematical proofs and examples, we show that if d²ⁿ(R) = 0 for some n ∈ N, then d²ⁿ⁻¹(R) = 0. Consequently, every nonzero nilpotent Jordan derivation has an odd nilpotency index. In addition, for a nilpotent element P ∈ R with nilpotency index n, the inner derivation dₚ(x) = [p, x] is nilpotent with nilpotency index at most 2n − 1. These results contribute to a deeper understanding of derivation structures on 2-torsion-free semiprime rings.